Negative Predictive Value of Mri-Detected Medial Meniscus Tears is Reduced in Young Athletes with Chronic ACL Injury. Issue 5 (31st May 2022) - Sliepka, Joseph; Hagen, Mia; Battan, Shamele; Kweon, Chris; Gee, Albert; Schmale, Gregory; Saper, Michael
Background: A delay in anterior cruciate ligament reconstruction (ACLR) is associated with an increase in the prevalence in medial meniscus tears identified at the time of surgery. However, the specific effect of time on the predictive value of magnetic resonance imaging (MRI) for detecting meniscus injury in the young athletic population with ACL tears is unclear. Purpose: To investigate the effect of time from MRI to ACLR on the predictive value of MRI to detect meniscus tears in adolescent and young adult athletes. Methods: A retrospective review was performed of patients aged 13-25 years who underwent primary ACLR at an academic institution from January 2017 to June 2020. Multi-ligament injuries were excluded. Primary data recorded included time from MRI to surgery and descriptions of medial and lateral meniscus tears on both MRI and operative reports. Time from MRI to surgery was divided into four intervals: 0 to 6 weeks, 6 weeks to 3 months, 3 months to 6 months, and beyond 6 months. Multivariable analysis was used to determine the positive (PPV) and negative predictive value (NPV) of MRI in detecting meniscus tears as compared to arthroscopic findings at each of the 4 time intervals. Results: 432 patients (54% female) were included with a mean age of 18 ± 3.4 years. The mean time from injury to MRI was 78 ± 187 days; the mean time from MRI to surgery was 71 ± 98 days. 252 patients had pre-operative MRIs without meniscus tears; 33 (13.1%) of those had a medial meniscus tear identified at the time of surgery (Table 1). New medial meniscus tears (100% vertical tears) were identified in 7/18 (38.9%) patients with surgery 6 months from MRI. There was a statistically significant decrease in the NPV of MRI to identify medial meniscus tears in patients who underwent ACLR greater than 6 months after imaging (odds ratio 0.16 [0.05–0.53], P < 0.005). Age, gender, body mass index, mechanism of injury, primary sport, and ethnicity did not affect the predictive value of MRI. Sensitivity and specificity of MRI to predict a medial meniscus tear in the entire cohort was 79% and 80%, respectively. Conclusion: Surgeons should counsel patients preoperatively about increased possibility of undiagnosed medial meniscus tears being found at the time of ACLR if greater than 6 months have passed from MRI to surgery. Table 1. Breakdown of Medial Meniscus Tears by Time from MRI until Surgery